The Relationship among Nutritional Status, Motor Ability, and Student Learning Achievements - Solissa, Jonas (Universitas Pendidikan Indonesia, 2020)
This study was aimed at examining the relationship between nutritional status, motor skills, and students’ learning achievements in Taekwondo subject. This research was conducted in Physical Education, Health, and Recreation Study Program of Pattimura University, Ambon 2019. The samples of the study were 51 students chosen by using total sampling technique. The instrument used for data collection on nutritional status of students was the Anthropometry Index (BB/TB). For motor skills, the Barrow Motor Ability test was used, while learning achievement was taken from the 2018 odd semester test scores. The results of data analysis showed that: 1) there was a positive relationship between nutritional status and student achievement in Taekwondo subjects. 2) There was a positive relationship between motor skills and students’ achievements in Taekwondo subjects. 3) There was a positive relationship between nutritional status and motor skills and students’ achievements in Taekwondo subject.